2016
DOI: 10.4038/tar.v27i3.8206
|View full text |Cite
|
Sign up to set email alerts
|

Phenolic content and antioxidant capacity of selected underutilized fruits grown in Sri Lanka

Abstract: The present study was carried out to evaluate the total phenolic content and antioxidant properties of four selected underutilized fruits species: Manilkara hexandra (Roxb.) Dubard (Palu), Salacia chinensis L. (Himbutu), Schleichera oleosa (Lour.) Oken (Koan) and Eugenia uniflora (Cherry) grown in Sri Lanka. Antioxidative constituents were extracted into water and the antioxidant activity of fruit extracts was assessed using biochemical assays: 1,1-diphenyl-2(2,4,6-trinitrophenyl) hydrazine (DPPH) radical scav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 17 publications
2
10
0
Order By: Relevance
“…Indeed, the aqueous extracts are more relevant and are being able to simulate the way of consumption since fruits are eaten in raw or used as fresh juice. In this study fruit extracts were refluxed for four hours for the maximum extraction of active phytochemicals to the relevant extract 21 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the aqueous extracts are more relevant and are being able to simulate the way of consumption since fruits are eaten in raw or used as fresh juice. In this study fruit extracts were refluxed for four hours for the maximum extraction of active phytochemicals to the relevant extract 21 .…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant efficiency is measured at ambient temperature, therefore that the risk of thermal degradation of the molecules tested is eliminated. The advantage of this method is that DPPH is allowed to react with the whole sample and sufficient time is given in the method which allows DPPH to react slowly even with weak free radical scavengers 21 . However, it has some limitations due to DPPH radical interaction with other radicals and the time response curve to reach the steady state is not linear with different ratios of antioxidant/DPPH 13 The FRAP assay is inexpensive and reagents are simple to prepare.…”
Section: Resultsmentioning
confidence: 99%
“…A number of local fruits grown in Sri Lanka has been identified as an excellent source of natural antioxidants. Moreover, many underutilized fruits exhibit greater amounts of promising antioxidant properties than commonly consumed fruits (Piyathunga et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Fruits and plant-based products have been used for food and medicinal purposes since the first human civilizations and indeed since the evolutionary origin of humans [ 1 3 ]. There is an emerging trend to consume more fruit on a regular basis, in response to the fact that fruits help to promote human health through supplying essential nutrients, improving immunity functions, and reducing the risk of many noncommunicable diseases (NCDs) such as cancers, diabetes mellitus, arthritis, Alzheimer's disease, Parkinson's disease in both developed, and developing countries [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Underutilized fruits of Sri Lanka are poorly studied and appreciated. The few studies available, published by various local researchers, have highlighted, for example, the antioxidant capacity of selected fruits grown in Sri Lanka [ 3 – 13 ]. In addition, one recent study has been reported on vitamin C contents and in-vitro antioxidant activities of selected Sri Lankan fruits including some underutilized fruits by Silva and Sirasa [ 14 ].…”
Section: Introductionmentioning
confidence: 99%